Mast Cell Chymase Degrades the Alarmins Heat Shock Protein 70, Biglycan, HMGB1, and Interleukin-33 (IL-33) and Limits Danger-induced Inflammation - Ananya Roy; Goutham Ganesh; Helena Sippola; Sara Bolin; Osama Sawesi; Anders Dagälv; Susan Schlenner; Thorsten B. Feyerabend; Hans-Reimer Rodewald; Lena Kjellén; Lars Hellman; Magnus Åbrink (2013)
During infection and tissue damage, virulence factors and alarmins are pro-inflammatory and induce activation of various immune cells including macrophages and mast cells (MCs). Activated MCs instantly release preformed inflammatory mediators, including several proteases. The chymase mouse mast cell protease (MCPT)-4 is thought to be pro-inflammatory, whereas human chymase also degrades pro-inflammatory cytokines, suggesting that chymase instead limits inflammation. Here we explored the contribution of MCPT4 and human chymase to the control of danger-induced inflammation. We found that protein extracts from wild type (WT), carboxypeptidase A3-, and MCPT6-deficient mice and MCs and recombinant human chymase efficiently degrade the Trichinella spiralis virulence factor heat shock protein 70 (Hsp70) as well as endogenous Hsp70. MC-(Wsash)-, serglycin-, NDST2-, and MCPT4-deficient extracts lacked this capacity, indicating that chymase is responsible for the degradation. Chymase, but not MC tryptase, also degraded other alarmins, i.e. biglycan, HMGB1, and IL-33, a degradation that was efficiently blocked by the chymase inhibitor chymostatin. IL-7, IL-22, GM-CSF, and CCL2 were resistant to chymase degradation. MCPT4-deficient conditions ex vivo and in vivo showed no reduction in added Hsp70 and only minor reduction of IL-33. Peritoneal challenge with Hsp70 resulted in increased neutrophil recruitment and TNF-α levels in the MCPT4-deficient mice, whereas IL-6 and CCL2 levels were similar to the levels found in WT mice. The rapid and MC chymase-specific degradation of virulence factors and alarmins may depend on the presence of accessible extended recognition cleavage sites in target substrates and suggests a protective and regulatory role of MC chymase during danger-induced inflammation. During infection and tissue damage, virulence factors and alarmins are pro-inflammatory and induce activation of various immune cells including macrophages and mast cells (MCs). Activated MCs instantly release preformed inflammatory mediators, including several proteases. The chymase mouse mast cell protease (MCPT)-4 is thought to be pro-inflammatory, whereas human chymase also degrades pro-inflammatory cytokines, suggesting that chymase instead limits inflammation. Here we explored the contribution of MCPT4 and human chymase to the control of danger-induced inflammation. We found that protein extracts from wild type (WT), carboxypeptidase A3-, and MCPT6-deficient mice and MCs and recombinant human chymase efficiently degrade the Trichinella spiralis virulence factor heat shock protein 70 (Hsp70) as well as endogenous Hsp70. MC-(Wsash)-, serglycin-, NDST2-, and MCPT4-deficient extracts lacked this capacity, indicating that chymase is responsible for the degradation. Chymase, but not MC tryptase, also degraded other alarmins, i.e. biglycan, HMGB1, and IL-33, a degradation that was efficiently blocked by the chymase inhibitor chymostatin. IL-7, IL-22, GM-CSF, and CCL2 were resistant to chymase degradation. MCPT4-deficient conditions ex vivo and in vivo showed no reduction in added Hsp70 and only minor reduction of IL-33. Peritoneal challenge with Hsp70 resulted in increased neutrophil recruitment and TNF-α levels in the MCPT4-deficient mice, whereas IL-6 and CCL2 levels were similar to the levels found in WT mice. The rapid and MC chymase-specific degradation of virulence factors and alarmins may depend on the presence of accessible extended recognition cleavage sites in target substrates and suggests a protective and regulatory role of MC chymase during danger-induced inflammation.